Evaluation of Irrigation Water Quality in Gölbaşı District - Gökşen Çapar; Çiğdem Coşkun Dilcan; Cenk Akşit; Şebnem Arslan; Mehmet Çelik; Süleyman Kodal (Journal of Agricultural Sciences)
Gölbaşı district, located at 20 km south of Ankara city is one of the special environmental protection areas SEPA of Turkey. The water resources of Golbasi district are under the pressure of urbanization and agricultural activities. In recent years, the demand for groundwater has increased, however accesibility is limited by the quantity and quality of water. This study aims to evaluate the irrigation water quality in Golbasi SEPA. A total of 41 water samples were collected from existing wells and fountains in 11 villages of Golbasi SEPA and analyzed for relevant quality parameters to assess their conformity with irrigation water quality standards. Analysis of samples led to classification of samples into 19 groups with common characteristics. Among them, 20 samples in Group 1-5 had salinity and alkalinity class of C2-S1, and they had the best water quality. On the other hand, 15 samples in Groups 6-14 had salinity and alkalinity class of C3-S1. Since these waters have high level of salt, leaching and special soil tillage is required to avoid salinity problem on the long-term. Yield reduction up to 10-25% may be experienced with alfalfa and corn. Among the samples, only 6 waters had salinity class of C4, and alkalinity of S1, S2 or S4. These waters are not suitable for irrigation under normal conditions. In special cases, they can be used if salt resistant plants are selected, where drainage is good and excess leaching is applied. Land reclamation may be required on the long term. Yield reduction up to 25-50% may be experienced with alfalfa and corn due to salinity